Impact of silver nanoparticles on benthic prokaryotes in heavy metal-contaminated estuarine sediments in a tropical environment. Issue 1 (15th October 2015) - Antizar-Ladislao, B.; Bhattacharya, B.D.; Ray Chaudhuri, S.; Sarkar, S.K.
Highlights: Some microbial communities in estuarine systems may be resistant to Ag-NPs. Ag-NPs stress can have an antimicrobial effect on key microorganisms. Ag-NPs have the potential to shape estuarine sediment bacterial community structure. Abstract: Little knowledge is available about the potential impact of commercial silver nanoparticles (Ag-NPs) on estuarine microbial communities. The Hugli river estuary, India, is susceptible to heavy metals pollution through boat traffic, and there is the potential for Ag-NP exposure via effluent discharged from ongoing municipal and industrial activities located in close proximity. This study investigated the effects of commercial Ag-NPs on native microbial communities in estuarine sediments collected from five stations, using terminal restriction fragment length polymorphism (T-RFLP) technique. An increase in the number of bacteria in consortium in sediments was observed following exposure to Ag-NPs. In general microbial communities may be resistant in estuarine systems to the antimicrobial effects of commercial Ag-NPs, but key microorganisms, such as Pelobacter propionicus, disappeared following exposure to Ag-NPs. In conclusion, the T-RFLP analysis indicated that Ag-NPs have the potential to shape estuarine sediment bacterial community structure.